Enhancement the Legal Regulation of the Activities of Local Administration amidst the Spread of Diseases Posing a Danger to the Population - Abdulridha Jaafar Naser Abdulridha; Sweedi Sattar Jabbar Zayer; Shaikhullin Marat Selirovich (Eximia, 2024)
This article examines the current theme of improving the public authority activities in the context of the spread of diseases that pose a particular danger to people. This research is aimed at studying the legal and organizational measures taken by public authorities, municipalities in the context of the spread diseases that pose a threat to all countries world -wide. The article analyzes the authorities of public bodies and the rights of citizens in connection with the provision of operational measures targeted at prevention, restraint, averting of dangerous diseases. The crucial role and responsibility of public authorities to ensure the sphere of citizens’ health protection and provide medical assistance to the population is specified. The assessment of the medical care availability in urgent situations is effected. The issues of creating conditions for the provision of high quality, qualified, prompt medical care to people are considered. The study has identified shortcomings in the activities of public authorities in timely response to violations of citizens' rights in the field of health care. It also pays attention to taking measures to reduce death rates, providing high-quality medications, conditions of sanitary and epidemiological well-being of the population, since these important factors affect the degree of stability of social and industrial activities, the country economy, direct communication in household and economic activities.